Semantic network analysis of spatial gene sequence in Dabaodao neighbourhood - Jun Dong; Haixiang Shang; Hang Yin (Journal of Asian Architecture and Building Engineering, 2024)
Dabaodao neighbourhood was a central gathering place of Chinese in the period of German colonial rule in Qingdao (north-eastern China), so the style and form of it express the integration of Chinese and Western cultures. With the help of the semantic network method, this paper proposes a gene analysis method suitable for historic neighbourhoods and analyses the genetic heritability of the Dabaodao neighbourhood. Regarding specific content, the spatial genes of the Dabaodao neighbourhood are identified as the primary research object, and two genetic research samples are proposed. Next, the spatial texture of the neighbourhoods is analysed to construct a semantic network model. Finally, with the help of the topological quantification method, a specific gene sequence analysis of the Dabaodao neighbourhood is conducted to discuss the degree of genetic influence expressed by it. On this basis, the effectiveness of gene analysis in neighbourhood renewal is discussed in the context of the renewal in the Dabaodao neighbourhood. Semantic network gene analysis not only provides an indicative strategy for the renewal of the Dabaodao neighbourhood but is also a formal analysis method different from the traditional quantitative analysis.